Flower and Spikelet Construction in Rapateaceae (Poales) - Koblova, Sofia D.; Rudall, Paula J.; Sokoloff, Dmitry D.; Stevenson, Dennis W.; Remizowa, Margarita V. (Frontiers in Plant Science, 2022)
The family Rapateaceae represents an early-divergent lineage of Poales with biotically pollinated showy flowers. We investigate developmental morphology and anatomy in all three subfamilies and five tribes of Rapateaceae to distinguish between contrasting hypotheses on spikelet morphology and to address questions on the presence of nectaries and gynoecium structure. We support an interpretation of the partial inflorescence (commonly termed spikelet), as a uniaxial system composed of a terminal flower and numerous empty phyllomes. A terminal flower in an inflorescence unit is an autapomorphic feature of Rapateaceae. The gynoecium consists of synascidiate, symplicate and usually asymplicate zones, with gynoecium formation encompassing congenital and often also postgenital fusions between carpels. Species of Rapateaceae differ in the relative lengths of the gynoecial zones, the presence or absence of postgenital fusion between the carpels and placentation in the ascidiate or plicate carpel zones. In contrast with previous reports, septal nectaries are lacking in all species. The bird-pollinated tribe Schoenocephalieae is characterized by congenital syncarpy; it displays an unusual type of gynoecial (non-septal) nectary represented by a secretory epidermis at the gynoecium base.